Analisa dan Perancangan Website Desa Sebagai Sistem Informasi dan Inovasi di Desa Sokawera, Kecamatan Somagede - Amanda Fitria Desvita; Ariska Nurul Habibah; Dwi Yuliana; Ilham Albana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In the current era of globalization, regional autonomy has become a very important part of public services. There is a need to address the problems that arise in Sokawera Village regarding the lack of facilities and skill level of village officials with the demands of a more dynamic community and an archival processing system that is still conventional. With the conveniences provided, it encourages people to utilize information and communication technology to help with their daily activities. The village government does not yet have a website address. This means that the information held by the village cannot be accessed by the wider community, causing Sokawera Village to still be very underdeveloped. In the era of increasingly advanced technology, a website-based information system can be implemented in Sokawera Village to overcome obstacles that can be used as a medium for village information and innovation. With the existence of a village information system in Sokawera Village, the community can directly access various kinds of information presented. Likewise, village officials can directly provide or update information related to the villages they support. All forms of information regarding purchasing products produced by local MSMEs can also be accessed on the village information system page. The methods used in this research are problem formulation, data collection, problem identification, system development using research results method.